CORPORATE SOCIAL RESPONSIBILITY IN THE BRAZILIAN ELECTRIC POWER SECTOR: INSTITUTIONAL, SECTORAL AND FIRM FACTORS - Goncalves, Karina (2012)
This case study aims to understand the institutional pressures that can determine socially responsible corporate behaviours of organisations that operate in the Brazilian electric power sector. It draws on New Institutional Sociology, specifically on Campbell´s (2006; 2007) propositions to analyse pressures on Brazilian electricity companies to behave in socially responsible ways. The empirical research employed included a questionnaire and document analysis (e.g. industrial regulations, companies´ websites and CSR / Sustainability reports). The research is institutionally supported by the Brazilian Association of Electric Power Companies (ABCE), who has sent the questionnaires on their behalf to member companies, specifically to CSR / Sustainability managers and assistants. The 14 respondent firms represent the variety of activities in which electricity companies operate in Brazil (i.e. generation, transmission, distribution, and research & development). Socially responsible corporate behaviours of Brazilian electricity companies are due not only to internal decisions based on economic rationality, but also to various coercive, normative and mimetic institutional pressures. Conditions under which organisations behave in socially responsible ways are contrasted in the case of Brazilian electricity companies – for instance, the enforcement by state regulations, the presence of industrial self-regulation, the monitoring of their corporate behaviour and their participation in associations that promote Corporate Social Responsibility.